PENERAPAN MEDIA PEMBELAJARAN KONSEP DASAR GEOGRAFI MENGGUNAKAN POSTER INFOGRAFIS BERBASIS APLIKASI CANVADI SMAN 6 PADANG - Afriyalni Syafril; Ratna Wilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Geography learning in senior high schools still faces challenges, particularly low student interest and understanding of basic geography concepts due to limited and teacher-centered learning media. This study aims to develop and implement infographic poster learning media based on the Canva application and to determine its feasibility and students’ responses. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted with tenth-grade students of Phase E9 at SMA Negeri 6 Padang from June to July 2025. Data were collected through interviews, questionnaires, and documentation, and analyzed using a Likert scale. The results indicate that the Canva-based infographic poster media was validated by subject-matter experts and considered suitable for geography learning. Students’ responses were categorized as very good, showing increased learning interest, engagement, and understanding of basic geography concepts. In conclusion, the implementation of Canva-based infographic poster media is effective in supporting geography learning. The findings imply that technology-based visual learning media can serve as an innovative alternative to enhance learning quality and support interactive, student-centered learning environments.